Pandangan Pimpinan Dayah Aceh Terhadap Kepemimpinan Non-Muslim - Widia Ningsih; Husnaini Husnaini (TANFIDZIY, 2023)
Choosing a non-Muslim leader is a polemic in society, especially Aceh as an area of legalization of the implementation of Islamic law in Indonesia. Of course this will be an issue of controversy in the Acehnese community itself. This type of research includes empirical juridical research. The results of this study explain that based on the Qur'an and the opinions of classical scholars clearly reject and do not allow choosing non-Muslim leaders on the basis of maintaining Islamic aqidah. While Abati Muhammad Nuruddin as one of the leaders of the Darul Ulum dayah in Kuta Makmur District, North Aceh argues that he also rejects non-Muslim leaders but with the assumption that what happened then and now is different. currently Indonesia uses a democratic government system, especially the presence of human rights makes anyone have the same rights when they want or are being a leader while still paying attention to existing restrictions. So that at this time, the concept of non-Muslim leadership in Indonesia cannot be prohibited.